Mapping the vulnerability of banana production landscapes in Uganda to banana bunchy top disease - Ocimati, Walter; Ogwal, Geofrey; Tazuba, Anthony Fredrick Kadama; Kubiriba, Jerome; Tugume, Joab; Rockefeller, Erima; Okurut, Wilson; Mahuku, George; Kutunga, David; Blomme, Guy (Frontiers Media, 2024)
Introduction: Banana bunchy top disease (BBTD) caused by banana bunchy top virus (BBTV) poses a significant threat to Uganda’s food and income security.